Relative contributions of diabetes and chronic kidney disease to neuropathy development in diabetic nephropathy patients. Issue 11 (November 2019) - Issar, Tushar; Arnold, Ria; Kwai, Natalie C.G.; Walker, Susan; Yan, Aimy; Borire, Adeniyi A.; Poynten, Ann M.; Pussell, Bruce A.; Endre, Zoltan H.; Kiernan, Matthew C.; Krishnan, Arun V.
Highlights: Patients with DKD manifest a more severe neuropathy phenotype and greater nerve dysfunction. The pathophysiological mechanisms between DKD and CKD are similar. These findings suggest that CKD and not T2DM propels axonal dysfunction in DKD. Abstract: Objective: Chronic kidney disease (CKD) caused by diabetes is known as diabetic kidney disease (DKD). The present study aimed to examine the underlying mechanisms of axonal dysfunction and features of neuropathy in DKD compared to CKD and type 2 diabetes (T2DM) alone. Methods: Patients with DKD ( n = 30), CKD ( n = 28) or T2DM ( n = 40) and healthy controls ( n = 41) underwent nerve excitability assessments to examine axonal function. Neuropathy was assessed using the Total Neuropathy Score. A validated mathematical model of human axons was utilised to provide an indication of the underlying causes of nerve pathophysiology. Results: Total neuropathy score was significantly higher in patients with DKD compared to those with either CKD or T2DM ( p < 0.05). In DKD, nerve excitability measures (S2 accommodation and superexcitability, p < 0.05) were more severely affected compared to both CKD and T2DM and worsened with increasing serum K + ( p < 0.01). Mathematical modelling indicated the basis for nerve dysfunction in DKD was an elevation of extracellular K + and reductions in Na + permeability and the hyperpolarisation-activated cation current, which was similar to CKD. Conclusions: Patients with DKD manifested a more severe neuropathy phenotype and shared features of nerve dysfunction to that of CKD. Significance: The CKD, and not diabetes component, appears to underlie axonal pathophysiology in DKD.